1994
DOI: 10.1177/089033449401000316
|View full text |Cite
|
Sign up to set email alerts
|

Incoordination of Sucking, Swallowing, and Breathing as an Etiology for Breastfeeding Difficulty

Abstract: This case report describes an infant who presented with coughing and choking during breastfeeding. Comprehensive clinical evaluation of these difficulties included assessment of sucking, swallowing, and breathing. Stridor and difficulty interspersing breaths during sucking bursts were observed, although sucking mechanics were normal. Further evaluation of airway structure revealed asymmetric laryngomalacia. This structural problem, exacerbated by the breastfeeding position, impeded respiration and resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…24 Some authors suggest that stimulation of suckling with the finger, preferable over cup-feeding, can facilitate adaptation to the movements of breast suckling. 30 The great difficulty in establishing and maintaining breastfeeding in preterm infants may be exemplified by the data obtained in our service. We observed that 58.3% of preterm infants with a birth weight below 1500 g were never breastfed.…”
Section: Discussionmentioning
confidence: 90%
“…24 Some authors suggest that stimulation of suckling with the finger, preferable over cup-feeding, can facilitate adaptation to the movements of breast suckling. 30 The great difficulty in establishing and maintaining breastfeeding in preterm infants may be exemplified by the data obtained in our service. We observed that 58.3% of preterm infants with a birth weight below 1500 g were never breastfed.…”
Section: Discussionmentioning
confidence: 90%
“…Infant feed volume or milk transfer was extremely variable. In week 1, the median milk volume consumed from 1 breast was 45 mL (range, 25-115), with median feed duration of 10.5 minutes (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], producing a median milk transfer of 5 mL/min (range, 1-19). At week 4, the median milk volume consumed from 1 breast was 68 mL (range, 30-240), with median feed duration of 11.5 minutes (range, 3-30), producing a median milk transfer of 7 mL/min (range, 2-30).…”
Section: Resultsmentioning
confidence: 99%
“…2,4,[7][8][9][10][11][12][13][14] Other investigators have characterized sucking by measuring pressure gradients in milk ducts plus intraoral pressures during sucking. 3,[15][16][17][18] Milk supply has also been measured. 19 Nipple position and its relationship to the hard-soft palate junction have not been measured.…”
mentioning
confidence: 99%
“…Blair et al 32 found that it is often a combination of several factors of the latch and positioning that contributes to sore nipples, including a partially closed mouth, nose and chin not in proximity to the breast, and nose not opposite to the nipple at latch. 43 A number of indicators of poor positioning and latch ( 44 Unless swallowing is validated (Table 5), the infant may not be receiving milk. Numerous prenatal and perinatal interventions can adversely affect latch [33][34][35][36][37][38][39][40][41][42] (Table 3), necessitating the referral to a lactation consultant if effective breast-feeding cannot be established within 36 to 48 hours of birth.…”
Section: Intervention Effectmentioning
confidence: 99%